Going offline - Keith, Jeremy (Book Apart (Series) ;, 2018)
Boldly take your website where it's never gone before: offline. Jeremy Keith introduces you to service workers (and the code behind them) to show you the latest strategies in offline pages. Learn the ins and outs of fetching and caching, enhance your website's performance, and create an ideal offline experience for every user, no matter their connection.